Introduction of Nomenclature of Territorial Units for Statistics in Croatia - Ivana Rasic (European Regional Science Association (ERSA), 2003)
The paper presents the process of introduction of the Nomenclature of Territorial Units for Statistics (NUTS) in Croatia. It will be discussed about all criteria that should be applied during that process of establishment and about constraints that disable reaching optimal solution. First constraint was the EUROSTAT's recommendation that the establishment of the Nomenclature of Territorial Units for Statistics should be based on the existing administrative division of the state territory. According to the main criteria (population size) the entire territory of the Republic of Croatia represents NUTS level I, existing counties NUTS level III, and the existing administrative units as municipalities and cities fulfil criteria of the establishment of NUTS IV level regions. As there are no administrative territorial units that correspond to NUTS level II, which is the main framework for the implementation of regional policy and the one competent for the analysis of regional problems and analyses, the most suitable solution is the formation of this level by combining counties. The biggest problem is how to define the NUTS II level. 1.Aggravating circumstance is the fact that in the Republic of Croatia a longer-lasting division in real regional units has never been established, which could serve as the basis for regional development policy. By this fact alone, the division of the territory of the Republic of Croatia in second level statistical units brings with it also a sensitive issue of regionalisation of Croatia and leads to political debates. To this contribute also the fact that the existing monitoring of statistical data on lower levels is not satisfactory, and the problem of data as the basis for quality economic analysis appeared. 2. In Croatia there are neither set regional boundaries nor a clearly defined regional policy. By introducing NUTS it would be possible to establish regional statistics as a basis for the formulation of regional policy. In the remainder the paper discusses main criteria which should be considered during the process of establishment regions as subject of regional policy. It presents how regionalisation depends on the criteria used and how different profession use different criteria. At the end, the final proposal of the Decision on the Nomenclature of Territorial Units for Statistics will be presented. Key words: regional policy, regionalisation
Keywords: 330